2019
DOI: 10.5923/j.ijmc.20190901.01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Linear Flow Velocity of Uncracked Ammonia (NH3) Gas on Formation of Higher Nitrides, 𝛅-MoN and 𝛆-Fe2N, under Concentrated Solar Irradiation in the SF40 Solar Furnace at PSA

Abstract: Nitriding experiments for powder specimens of Mo and Fe were carried out using a solar furnace SF40 at PSA (Plataforma Solar de AlmerĂ­a) in Tabernas (Spain) in uncracked ammonia NH 3 gas (NH 3 gas with suppressed extent of dissociation by flowing) aiming at determining the range of linear velocity v of NH 3 gas flow to yield higher nitride phases, ÎŽ-MoN for Mo and Δ-Fe 2 N for Fe. Standard solar exposure duration at a specified reaction temperature T was set to be 60 min over range of v between 1.14 mm‱s -1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Metal powders of V, Nb, and Ta were subjected to nitridation reactions in the solar furnace SF40, with the nominal power of 40 kW, at PSA [12] in flowing NH 3 gas (Figure 1). Details of the experimental procedures are identical to those described in the paper [11] published in 2019; the only difference are the tap-densified powders (instead of Mo and Fe powders [11], powders of V, Nb, and Ta were subjected to nitridation reactions). At the focal spot of the concentrated solar beam, the radiative flux reaches 7000 Suns (1 Sun = 1 kW‱m −2 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Metal powders of V, Nb, and Ta were subjected to nitridation reactions in the solar furnace SF40, with the nominal power of 40 kW, at PSA [12] in flowing NH 3 gas (Figure 1). Details of the experimental procedures are identical to those described in the paper [11] published in 2019; the only difference are the tap-densified powders (instead of Mo and Fe powders [11], powders of V, Nb, and Ta were subjected to nitridation reactions). At the focal spot of the concentrated solar beam, the radiative flux reaches 7000 Suns (1 Sun = 1 kW‱m −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, in such a configuration with a spherical reactor chamber, the effect of increasing extent of dissociation (α) of flowing NH 3 gas along the flow path from the upstream side to the downstream side was not evaluated. To overcome this problem, we developed a linear flow tube reactor and the first results acquired using this novel reactor setup were published in 2019 [11]. The experiment reported in [11] was done aiming at synthesizing higher nitrides, ÎŽ-MoN and Δ-Fe 2 N, respectively, of Mo and Fe in a stream of NH 3 gas with linear flow speed (v) between 1.14 and 11.4 mm‱s −1 under heating with concentrated solar beam using the solar furnace SF40 [12] at Plataforma Solar de AlmerĂ­a (PSA), Spain, at the processing temperatures T = 800 and 900 ‱ C for tap-densified (loosely compacted) powders of Mo specimen and T = 500 and 600 ‱ C for tap-densified powders of Fe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carrying out the solar experiments also in a stream of gas, which in this case was uncracked ammonia NH 3 gas (NH 3 gas with suppressed extent of dissociation by flowing), other researches [55] have shown that higher nitrides of Mo (ÎŽ-MoN) and Fe (Δ-Fe 2 N) can be successfully synthesized. For that they have developed an experimental setup consisting of a linear reaction tube made of silica glass and sample holder made of refractory steel in order to carry out nitriding experiments for powder specimens of Mo and Fe in uncracked NH 3 gas at specified linear flow rate under irradiation of concentrated solar beam.…”
mentioning
confidence: 99%